The Study of Effects of Thai Native Silkworm and Mulberry Varieties on Silk Production in Sakon Nakhon Province - มาศเมธาทิพย์, รุ่งทิพย์; คัมภีราวัฒน์, ภานุวัฒน์ (KKU Science Journal, 2013)
The study on growth and production of four Thai native silkworm varieties (Nangsew, Nangtui, Huacharuad, Samrhong) fed by using three difference mulberry varieties (Burirum 60, Sakon Nakhorn 10, Sakon Nakhorn 72) was under taken. The experimental design was 4×3 factorial in RCBD with four replications of block. The result showed that the Thai native silkworm varieties had significant effect on number of eggs per female, hatching percentage, early instar larvae survival percentage, full-grown instar larvae survival percentage, weight of fifth instar larvae, percentage of cocoon, percentage of complete pupae, fresh weight of cocoon, weight of cocoon shell, percentage of cocoon shell and silk length per cocoon (P<0.05). From this study, it was found overall that Nangtui had the highest growth and presented total product higher than other varieties. The mulberry varieties had significant effect only on early instar larvae survival percentage and weight of fifth instar larvae (P<0.01). Additionally, in this study represented that the correlation values were -0.81 to 0.93. Therefore, for the breeding program of Thai native silkworm variety, if it is considered only single trait, the result will affect on the other traits. However, it depends the correlation level.